Bovine parotid secretory protein: structure, expression and relatedness to other BPI (bactericidal/permeability-increasing protein)-like proteins. (1st August 2003) - Wheeler, T.T.; Hood, K.; Oden, K.; McCracken, J.; Morris, C.A.
Abstract : Members of the family of BPI (bactericidal/permeability-increasing protein)-like proteins are as yet incompletely characterized, particularly in cattle, where full-length sequence information is available for only three of the 13 family members known from other species. Structural bioinformatic analyses incorporating bovine homologues of several members of the BPI-like protein family, including two forms of bovine parotid secretory protein (PSP), showed that this family is also present in cattle. Expression analyses of several members of the BPI-like protein family in cattle, including PSP (Bsp30), von Ebner's minor salivary gland protein (VEMSGP) and lung-specific X protein (LUNX), showed a restricted pattern of expression, consistent with earlier hypotheses that these proteins function in the innate immune response to bacteria. The possible role of bovine PSP in susceptibility to pasture bloat in cattle is discussed.